보행접근성 분석에 기반한 근린공원의 공원서비스 평가 - 성남시 분당구를 대상으로 - 황해권; Hwang Hae-kwon; 손용훈; Son Yong-hoon (한국조경학회지, 2024)
도시화가 진행되면서 공원녹지에 대한 수요는 증가하고 있다. 공원녹지는 도시 내에서 사람들이 자유롭게 옥외활동을 할 수 있는 공간으로 인식되고 있어 중요한 공간이다. 공원서비스 권역은 거리를 기반으로 어느 범위까지 서비스를 제공하고 있는지를 보여주는 척도이다. 이 과정에서 접근성이라는 개념은 중요하게 작용하며 특히 보행은 사람의 가장 기본적인 이동수단으로서 공원 이용에 많은 영향을 미치고 있다. 하지만 현재 공원서비스 권역 분석은 소외지역을 발견하는 것에 중점을 두고 있어 수혜지역에 대한 세부적인 평가는 미비한 상황이다. 본 연구에서는 보행네트워크의 보행접근성을 바탕으로 공원서비스 권역을 평가하고자 한다. 공원서비스는 이용자가 직접 공원을 방문함으로써 발생하는 서비스로서 접근성이 이용 가능성으로 나타날 것으로 판단된다. 보행네트워크의 정량화를 위하여 본 연구에서는 공간구문론을 활용하여 통합도 값을 바탕으로 보행접근성 분석을 진행하였다. 통합도 값은 보행네트워크의 접근성 정도를 수치화하여 보여주는 지표로서 본 연구에서는 통합도 값이 높을수록 공원 이용 가능성이 높다고 해석하였다. 연구의 결과는 다음과 같다. 첫째, 분당구의 공원서비스 권역은 43%를 차지하고 있으며, 보행접근성이 높은 구간이 대부분 포함되어 있지만 일부 보행접근성이 좋은 구간은 제외되어 있다. 이는 도시계획 과정에서 주거지역과 상업 및 업무 지역이 우선적으로 지정되고 그 후에 공원녹지 지역이 선정되는 과정에서 나타나는 현상으로 볼 수 있다. 둘째, 분당구를 기준으로 공원서비스 권역 및 공원서비스 권역 내 보행접근성을 법정동별로 분류하였다. 개별 법정동 별로 차이가 나타나며, 이에 따른 공원에 대한 이용 가능성이 다르게 나타날 것으로 예상된다. 또한, 같은 도시계획 과정에서 만들어진 지역이라도 보행접근성에 따른 공원서비스 권역의 평가는 차이가 나타났다. 이를 활용하여 생활권 계획에 반영될 수 있는 개별 동 단위의 평가가 가능하며 추후 이를 반영한 공원녹지 정책에서 유용한 지표로 활용될 수 있다. As urbanization progresses, the demand for parks and green space is increasing. Park green spaces in the city are important spaces in the city because they are recognized as spaces where people can freely engage in outdoor activities. The park service area is a measure that shows the extent to which services are provided based on distance. In this process, the concept of accessibility plays an important role, and walking, in particular, as the most basic means of transportation for people and has a great influence on the use of parks. However, the current park service area analysis focuses on discovering underprivileged areas, so detailed evaluation of beneficiary areas is insufficient. This study seeks to evaluate park service areas based on the pedestrian accessibility and the pedestrian network. Park services are services that occur when users directly visit the park, and accessibility is expected to be reflected in terms of usability. To quantify the pedestrian network, this study used space syntax to analyze pedestrian accessibility based on integration values. The integration values are an indicators that quantify the level of accessibility of the pedestrian network, and in this study, the higher the integration value, the higher the possibility of park use. The results of the study are as follows. First, Bundang-gu's park service area accounts for 43%, and includes most sections with high pedestrian accessibility, but some sections with good pedestrian accessibility are excluded. This can be seen as a phenomenon that occurs when residential areas and commercial and business areas are given priority during the urban planning process, and then park and green areas are selected. Second, based on Bundang-gu, the park service area and pedestrian accessibility within the park service area were classified by neighborhood unit. Differences appear for each individual neighborhood unit, and it is expected that the availability of the park will vary accordingly. In addition, even in areas created during the same urban planning process, there were differences in the evaluation of park service areas according to pedestrian accessibility. Using this, it is possible to evaluate individual neighborhood units that can be reflected in living area plans, and it can be used as a useful indicator in park and green space policies that reflect this in the future.